Hocus pocus : a tale of magnificent magicians - Kieve, Paul.; Bailey, Peter, 1946- (New York : Scholastic Press, 2008)
A young Englishman, just starting his career as a magician, is helped by some of the greatest magicians in history as they step out of posters of themselves to help him master the tricks and techniques of the trade.
"Includes over 35 tricks!"--Cover.
Includes an envelope of post cards featuring different magicians and magic tricks p. 3 of cover.
Col. ill. on endpapers.
Includes bibliographical references (p. 296-297).
5.7
3-6
Keywords: Magicians -- Juvenile fiction; Magic tricks -- Juvenile fiction; Magicians -- Fiction; Magic tricks -- Fiction; Magicians -- Fiction; Magic tricks -- Fiction; Magicians -- Fiction; Magic tricks -- Fiction; London (England) -- Juvenile fiction; England -- Juvenile fiction; London (England) -- Fiction; England -- Fiction; London (England) -- Fiction; England -- Fiction; London (England) -- Fiction; England -- Fiction